THE EFFECT OF DICTOGLOSS TECHNIQUE ON THE STUDENTS’ WRITING SKILLS - Rikawati; Annisa Shofa Tsuraya; Masykur Rauf (ELTIES : English Language Teaching for EFL Learners, 2022)
This research aimed at finding out the effect of using Dictogloss Technique in improving students’ skills in news writing at the third grade students of MA Modern Tarbiyah Takalar in academic 2020/2021. This research employed a quasi-experimental research design. The population of this research was the third grade students of MA Modern Tarbiyah Takalar which consisted of 39 students. The sample of the research consisted of 36 students which were taken by using total Sampling, 18 students from XII A as control class and 18 students from XII B as experimental class. The instrument in this research was test that was given in pre-test and posttest. The data indicated that there was a significant difference between students’ posttest in experimental class and controlled class. The mean score of post-test (68.27) in experimental class was greater than the mean score of post-test (51.22) in controlled class. The standard deviation of post-test (13.1) in experimental class and(9.7) in controlled class. From t-test, the researcher found that the value of t-test (4.608) was greater than t-table (2.042) at the level of significance 0.05 with degreeof freedom (df) = 34. It proves that the use of Dictogloss technique was effective in improving the students’news writing text of the third grade students of MA Modern Tarbiyah Takalar in academic 2020/2021. Dictogloss gave opportunities for learners to learn as individuals and as a group by critical thinking, Students can sharp their learning autonomy. It happens in the group while the students work together to recreate the text by helping each other with their friends. Dictogloss is also useful for vocabulary acquisition and building students’ writing habits.